Experimental study of adjacency of direct and indirect inlays to dental tissue - Makeev, V.; Mykyyevych, N. (Actual Dentistry, 2018)
Summary. The research experimentally measures the degree of adjacency of direct and indirect inlays made of different types of composite materials to the dental tissue of lateral teeth. Indirect inlays have proved to have higher degree of adjacency as compared to direct ones. Key words: direct inlays, indirect inlays, adjacency to dental tissue